2009
DOI: 10.1520/jai102156
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adjuvants, Pesticide Formulation, and Spray Nozzle Tips on Spray Droplet Size

Abstract: Many factors, including adjuvants, pesticide formulations, and nozzle tips, affect spray droplet size. It is important to understand these factors as spray droplet size affects both drift and efficacy of pesticides, which is a main concern with pesticide application. A laser particle analyzer was used to determine the spray droplet size and distributions of a range of formulations sprayed through several types of nozzle tips. Nozzles included were extended range flat fan sizes 11003 and 11005 ͑Spraying Systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Many factors, including adjuvants, pesticide formulations and nozzle tips, affect spray droplet size [38]. Table 4 displays the effects of aviation spray adjuvants on defoliant cotton canopy spray quality parameters, namely dimension of droplet impacts, density and surface coverage.…”
Section: Effect Of Aviation Spray Adjuvants On Droplet Depositionmentioning
confidence: 99%
“…Many factors, including adjuvants, pesticide formulations and nozzle tips, affect spray droplet size [38]. Table 4 displays the effects of aviation spray adjuvants on defoliant cotton canopy spray quality parameters, namely dimension of droplet impacts, density and surface coverage.…”
Section: Effect Of Aviation Spray Adjuvants On Droplet Depositionmentioning
confidence: 99%
“…Many factors, including adjuvants, pesticide formulations, and nozzles affect spray droplet size (Klein et al, 2009 ). The droplet size is one of the important indicators to evaluate the spraying quality when using UAVs.…”
Section: Resultsmentioning
confidence: 99%
“…Spray adjuvants greatly influence on the deposition characteristics of spray droplets [24]. Xiao et al found that adding aviation spray adjuvant vegetable oil could significantly improve the defoliant droplet deposition on cotton leaves [20].…”
Section: Effect Of Aviation Spray Adjuvants On Droplet Depositionmentioning
confidence: 99%